Pengaruh Disiplin Kerja dan Etos Kerja terhadap Kinerja Karyawan di PT Rejeki Jaya Bike Karawang - Lidya Putri Permana; Aji Tuhagana; Zenita Apriani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine, analyze, and explain the influence of Work Discipline and Work Ethic on Employee Performance at PT Rejeki Jaya Bike Karawang located in Teluk jambe, Teluk jambe Timur District, Karawang Regency, West Java Province, with postal code 41361. This writing uses descriptive quantitative and qualitative methods, data collected through questionnaires given to 45 employees of PT Rejeki Jaya Bike Karawang and Using Multiple Linear Regression Analysis The results of this study indicate that the level of Work Discipline and Work Ethic of employees is classified as high X1 has a value of 0.825, namely variable X1 has a positive influence on variable Y, X2 has a value of 0.161, this indicates that variable X2 has a positive influence on variable Y. Partial tests reveal that both variables have a significant influence on Employee Performance X1 has a Sig value of 0.001 <0.05 and t count 25.050> 2.019, meaning that Work Discipline has a partial significant effect on Employee Performance, X2 has a Sig 0.001 <0.05 and t count 18.312 > 2.019 means that Work Ethic partially has a significant effect on Employee Performance. Meanwhile, the F count test has a sig value of 0.001 <0.05 and F count of 317.703 > 3.05. This means that the variables of work discipline and Work Ethic simultaneously have a significant effect on Employee Performance. The determination coefficient value of 0.938 indicates that simultaneously, Work Discipline and Work Ethic contribute 93.8% to the variation that occurs in the Employee Performance variable.